Non-redundant functions of two proline dehydrogenase isoforms in Arabidopsis - Funck, Dietmar (BioMed Central, 2010)
BACKGROUND: Proline (Pro) accumulation is a widespread response of prokaryotic and eukaryotic cells subjected to osmotic stress or dehydration. When the cells are released from stress, Pro is degraded to glutamate by Pro-dehydrogenase (ProDH) and Pyrroline-5-carboxylate dehydrogenase (P5CDH), which are both mitochondrial enzymes in eukaryotes. While P5CDH is a single copy gene in Arabidopsis, two ProDH genes have been identified in the genome. Until now, only ProDH1 (At3g30775) had been functionally characterised. RESULTS: We demonstrate vasculature specific expression of the Arabidopsis ProDH2 gene (At5g38710) as well as enzymatic activity and mitochondrial localisation of the encoded protein. Expression levels of ProDH2 are generally low, but increased in senescent leaves and in the abscission zone of floral organs. While sucrose represses ProDH2 expression, Pro and NaCl were identified as inducers. Endogenous ProDH2 expression was not able to overcome Pro sensitivity of ProDH1 mutants, but overexpression of a GFP-tagged form of ProDH2 enabled the utilisation of Pro as single nitrogen source for growth. Amongst two intronic insertion mutants, one was identified as a null allele, whereas the other still produced native ProDH2 transcripts. CONCLUSIONS: Arabidopsis possesses two functional ProDHs, which have non-redundant, although partially overlapping physiological functions. The two ProDH isoforms differ with respect to spatial, developmental and environmental regulation of expression. While ProDH1 appears to be the dominant isoform under most conditions and in most tissues, ProDH2 was specifically upregulated during salt stress, when ProDH1 was repressed. The characterisation of ProDH2 as a functional gene requires a careful re-analysis of mutants with a deletion of ProDH1, which were so far considered to be devoid of ProDH activity. We hypothesise that ProDH2 plays an important role in Pro homeostasis in the vasculature, especially under stress conditions that promote Pro accumulation.